Pemurnian Pasir Silika dengan Metode Leaching Asam dan bantuan Sonikasi - Sumarno Sumarno (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Silica sand is one of the natural materials that abundant in Indonesia . In nature, silica is difficult to obtain a high purity compound because it has a high affinity with the others oxide. Purification methode of silica can be done in several ways, one of which is sonication assisted acid leaching methode. In general, leaching medium used a strong acids such as HCl and H2SO4. The using of strong acids will produce waste that requires special handling as B3 waste. So in this research, used aquadest and oxalic acid as the leaching medium are more environmentally. The research have purpose to study the effect of sonication on purification process of silica sand with aquadest and oxalic acid leaching medium to obtain high purity silica sand. The product optained were analyzed by Scanning Electron Microscopy (SEM) and X-Ray Fluorescence (XRF). XRF analysis results showed that the content in the silica sand increased from 97.75% to 99.40% with aquadest leaching medium and 99.46% with oxalic acid leaching medium with the same sonication time is 120 minutes. While the results of SEM analysis showed morphological changes of silica sand after sonication process both with distilled water leaching media and with oxalic acid.